The Marriage Code and Traditional Village Administration of Mizo: Exploring the marriage code and administration structure in the traditional Mizo society (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The paper presented the marriage code of Mizo in the light of their traditional customs. It examines the procedure for marriage and divorce. In the administration, this paper highlighted the power and functions of the chief, elders, tlangau and the role of zawlbuk.